A Behavioral Analysis of Joint-Cost Allocation and Transfer Pricing (Book). - Burns, Thomas J.; Wilner, Neil A. (The Accounting Review, 1981)
Reviews the book "A Behavioral Analysis of Joint-Cost Allocation and Transfer Pricing," by Arthur L. Thomas.